2018
DOI: 10.18632/oncotarget.24286
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting checkpoint kinase 1 protects bone from bone resorption by mammary tumor in a mouse model

Abstract: DNA damage response plays a critical role in tumor growth, but little is known about its potential role in bone metabolism. We employed selective inhibitors of Chk1 and examined their effects on the proliferation and migration of mammary tumor cells as well as the development of osteoblasts and osteoclasts. Further, using a mouse model of bone metastasis we evaluated the effects of Chk1 inhibitors on bone quality. Chk1 inhibitors blocked the proliferation, survival, and migration of tumor cells in vitro and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…While the present results revealed a novel role for AZD7762 in bone remodeling and bone metastasis, the present study has certain limitations. The experiments herein employed mouse and human cell lines ( 11 ), and gene expression was primarily examined using monolayer cell cultures. Although clinical trials of AZD7762 are not going forward due to unpredictable cardiac toxicity, inhibition of Chk remains an important therapeutic target ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the present results revealed a novel role for AZD7762 in bone remodeling and bone metastasis, the present study has certain limitations. The experiments herein employed mouse and human cell lines ( 11 ), and gene expression was primarily examined using monolayer cell cultures. Although clinical trials of AZD7762 are not going forward due to unpredictable cardiac toxicity, inhibition of Chk remains an important therapeutic target ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…AZD7762 is a potent inhibitor of Chk1 and Chk2 that potentiates antitumor activity in xenograft models in a dose-dependent manner when simultaneously administered with DNA-damaging agents ( 9 ). PD407824 is a selective inhibitor of Chk1 ( 10 ), and its inhibitory effect on tumor growth and bone resorption was recently reported in connection to the regulation of stress in the endoplasmic reticulum (ER) ( 11 ). Chk1 is a primary gatekeeper of cell division at multiple cell cycle checkpoints, including the S, G2/M and M phases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the effects of Chk1 inhibitors on tumor cells have been reported (18), their role in development of bone-forming osteoblasts and bone-resorbing osteoclasts need to be examined. In our previous study, we conducted in vitro and in vivo analysis for evaluating the role of PD407824 on MC3T3 osteoblast-like cells as well as RAW264.7 pre-osteoclast cells and found that PD407824 is an effective inhibitor of bone degradation in addition to its anti-tumor effects (14). The current study further supports its potential benefit in preserving bone mechanical properties from degradation by metastatic tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of Chk1 results in cell cycle arrest, and its mutations are reported to be linked to breast and other cancers (11). Administration of Chk inhibitors for inhibiting tumor growth has been considered (12, 13), and we recently reported the effects of these inhibitors on suppression of bone resorption (14). In this report, we showed that Chk1 inhibitors blocked the proliferation, survival, and migration of tumor cells in vitro and suppressed the development of bone-resorbing osteoclasts by downregulating nuclear factor of activated T cells (NFATc1), a master transcription factor for osteoclast development.…”
Section: Introductionmentioning
confidence: 99%